Classical liberalism and international economic order : studies in theory and intellectual history - Sally, Razeen, 1965- (Routledge advances in international political economy ;, 2002)
This book makes an innovative link between classical liberalism and questions of international economic order. The author begins with an outline of classical liberalism as applied to domestic economic order. He then surveys the classical liberal tradition from the Scottish Enlightenment to modern thinkers like Knight, Hayekn and Viner. Finally, he brings together the insights of thinkers in this tradition to provide a synthetic overview of classical liberalism and international economic order. The author's deployment of classical liberalism strikes a different note to other 'liberal' interp.